Bias Gender dalam Buku Bahasa Arab Siswa MA Kelas X dengan Pendekatan Saintifik 2013 - Shodiq, Muhammad Jafar (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
Gender is the difference of men and women in the role, function, right, responsibility and behavior which is made by social and cultural value, and tradition. Gender bias is the circumstance that indicates male attitude more than female. This article is intended to determine gender bias in the book of Arabic class X that is written and based on a scientific approach as the curriculum characteristic in 2013. Student Books which are used as the principal teaching materials by their teacher, are very important in supporting the learning process.The findings of data analysis show that it has still been happening gender bias in the book in the form of pictures and texts.